The effects of weight loss on imaging outcomes in osteoarthritis of the hip or knee in people who are overweight or obese: a systematic review. Issue 1 (January 2020) - Daugaard, C.L.; Hangaard, S.; Bartels, E.M.; Gudbergsen, H.; Christensen, R.; Bliddal, H.; Englund, M.; Conaghan, P.G.; Boesen, M.
Summary: Objective: To evaluate the structural effects of weight loss on hip or knee osteoarthritis (OA) and to summarize which structural joint pathologies have been examined and the evidence for the outcome measurement instruments applied. Design: Based on a pre-specified protocol (available: PROSPERO CRD42017065263), we conducted a systematic search of the bibliographic databases, Medline, Embase and Web of Science identifying longitudinal articles reporting the effects of weight loss on structural imaging outcomes in OA of the hip or knee in people who are overweight or obese. Results: From 1625 potentially eligible records, 14 articles (from 6 cohorts) were included. 2 cohorts were derived from RCTs. Evaluated pathologies were: articular cartilage ( n = 7), joint space width ( n = 3), bone marrow lesions ( n = 5), synovitis ( n = 2), effusion ( n = 1), meniscus ( n = 3), bone marrow density ( n = 1) and infrapatellar fat pad (IPFP; n = 2). Cartilage showed conflicting results when evaluating cartilage thickness by direct thickness measurements. Compositional dGEMRIC and T2 mapping measures in early knee OA showed trends towards reduced cartilage degeneration. Joint space width on conventional radiographs showed no change. Weight loss reduced the size of the IPFP. Synovitis and effusion were not affected. Following weight loss DXA showed bone loss at the hip. Conclusion: We did not find consistent evidence of the effects of weight loss on OA structural pathology in people who are overweight or obese. There is a need to achieve consensus on which structural pathologies and measurements to apply in weight loss and OA research.